Impactos da COVID-19 na produção científica dos Programas de Pós-graduação em Educação Física - Sarah Jane Lemos de Melo (2024)
The COVID-19 pandemic has brought about significant societal transformations, particularly in the educational landscape, compelling physical education professionals to embrace online training. Despite these changes, the impact of the pandemic on the scientific production of physical education researchers remains underexplored. This study analyzed the curricula of 558 Brazilian researchers across 27 postgraduate programs in Physical Education, aiming to investigate the potential impact of the pandemic on scientific publications. Analyses were conducted in a virtual environment using publicly available data from the postgraduate program websites and respective curriculum vitae. Researchers' production from 2018 to 2022 underwent a comprehensive analysis, considering the total number of publications, the Qualis classification (a Brazilian index evaluating study quality), and the Clarivate Journal Impact Factor. Data were analyzed using Chi-Squared and Kruskall-Wallis tests, with a significance level of 5%. In total, researchers published 17,932 manuscripts during the mentioned period. During the COVID-19 pandemic, there was a 16.4% reduction in the number of articles published (P = 0.001). This decrease was similar between men and women (P = 0.603) and associated with a deterioration in the Qualis ranking (P = 0.001). Conversely, the Clarivate Journal Impact Factor of the journals where manuscripts were published remained stable (P = 0.275). Regarding researchers' profiles, the majority had a degree in Physical Education, and it is noteworthy that 68% of the faculty are male, with an even more pronounced imbalance among scholarship holders, with 79% being male. Beyond the stated objectives, another concerning aspect revealed by the analysis was the disparity in the number of doctorates among regions, with the Northeast having the lowest quantity. The results suggest a potential impact of the pandemic on the scientific production of physical education researchers in all regions and across genders. Funding agencies should consider the challenges associated with the pandemic when evaluating academic work and research programs.